Pengaruh Sekularisme terhadap Ilmu Modern Saat Ini - Sumiran; Rocyayah, Anita; Muzhaffar, Zidan Arif; Mabruroh , Nurul; Pratiwi, Aprilia Ayu (Jurnal Penelitian Tarbawi: Pendidikan Islam dan Isu-Isu Sosial, 2026)
Secularism is an ideology that separates religion from worldly life, including the field of science. This paradigm emerged from the historical experience of Western society in its attempt to liberate science from the domination of the Church during the Middle Ages. However, over time, secularism developed into a worldview that marginalizes the role of divine revelation in the development of knowledge. This article aims to examine the nature and historical origins of secularism, analyze its impact on the development of modern science, and explain the Islamic perspective and alternative concepts of knowledge in responding to secularism. This study employs a qualitative descriptive method through a literature review of primary and secondary sources from both Western scholarship and classical as well as contemporary Islamic thought. The findings indicate that secularism has contributed to the emergence of value-free science, the loss of a tawhidic orientation, and moral and spiritual crises in modern human life. Islam views the separation of science and religion as contrary to the principle of tawhid, as knowledge in Islam is considered a divine trust that must be directed toward human well-being and devotion to Allah SWT. Therefore, Islam offers an alternative paradigm through the reinforcement of tawhid as the foundation of knowledge, the harmonious integration of revelation and reason, the cultivation of scholarly adab, and the concept of Islamization of knowledge. This paradigm is expected to produce scientific and technological advancement while remaining firmly grounded in moral and spiritual values.